HUBUNGAN ANTARA KETERLIBATAN KERJA DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA KARYAWAN YANG MENGGUNAKAN KOMPUTER DI PT SEMEN BATURAJA (PERSERO) PALEMBANG - Rina Oktaviana (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2019)
This study aims to determine the relationship between job involvement with organizational citizenship behavior (ocb) on employees. who use computers at PT. Semen Baturaja (Persero) Palembang. The dependent variable in this study is Organizational Citizenship Behavior (OCB) while Job Involvement as independent variable. This study uses the scale of Organizational Citizenship Behavior (OCB) and Job Involvement. This research uses quantitative method. The sample in this study as many as 146 employees of PT. Semen Baturaja (Persero) Tbk Palembang and data were analyzed using simple regression technique.